Faktor Yang Berhubungan Dengan Stunting Pada Balita Di Puskesmas Syamtalira Aron - US, Hafsah; AB, Myrna Lestari; Ernita, Ernita; Elvieta, Elvieta (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Stunting is a condition where children under the age of 5 cannot grow properly due to chronic malnutrition, leading to them being too short for their age. The aim of this study is to analyze factors related to the growth and development delay of toddlers in the Syamtalira Aron Community Health Center. The research design used a cross-sectional correlational approach on the population of mothers with stunted toddlers in the working area of the Syamtalira Aron Community Health Center. The sampling technique employed total sampling, and 38 mother-child pairs with stunting were obtained as research respondents. Data collection took place from October 18 to 29, 2021. The data were analyzed using Fisher's exact test (α=95%). The results showed a correlation between the mother's height (p = 0.014), family income (p = 0.000), and exclusive breastfeeding (p = 0.033) with the prevalence of stunting in toddlers. Meanwhile, the variable not associated was the mother's educational level (p = 0.062). In conclusion, the research indicates a correlation between the mother's height, family income, and exclusive breastfeeding with the incidence of stunting in toddlers. It is recommended that relevant authorities collaborate to prevent stunting early on. Mothers are encouraged to proactively engage in preventive efforts by increasing knowledge and awareness to control pregnancy, understanding how to achieve and meet the nutritional needs of toddlers, ensuring that the process of toddler growth and development is optimized.